Why Ireland? a qualitative review of the factors influencing the location of US multinationals in Ireland with particular reference to the impact of labour issues - Gunnigle, Patrick; McGuire, David (Economic & Social Studies, 2001)
The encouragement of foreign direct investment (FDI) represents a key plank of industrial policy in Ireland. This paper considers the impact of labour issues on the decision of US multinational corporations (MNCs) to locate facilities in Ireland. Drawing on data gathered in ten major US corporations, and from executives employed in the main industrial promotions agencies, this paper evaluates the relative impact of labour issues on the location of MNCs. While our findings point to the critical significance of Ireland?s low corporate tax regime in attracting US FDI to Ireland, they also identify the relative impact of issues such as labour supply, quality and cost, and broader human resource management factors such as labour flexibility and trade union recognition, on the location decision of inward investing MNCs.
Keywords: Industrial location; Multinational corporations; Labour force; Ireland; United States; Foreign direct investment